Gravitino cosmology helped by a right handed (s)neutrino - Gongjun Choi; Tsutomu T. Yanagida (Physics Letters B, 2022)
In this paper, we discuss interesting scenarios resulting from the interplay between the gravitino and the lightest right-handed (s)neutrino. We consider two gravitino mass regimes vastly separated, that is, m3/2=O(100) eV and m3/2≃100 GeV. For the former case, a significant amount of the entropy production in the cosmological history to dilute the gravitino relic abundance is unavoidable for consistency with the number of satellite galaxies in the Milky way. We will show that the right-handed (s)neutrino can play the role of the heavy particle whose late time decay provides such an additional radiation. For the later case, the gravitino of m3/2≃100 GeV may resolve the S8 tension as a decaying dark matter. We will show how the lightest right-handed neutrino and its superpartner can help the gravitino decaying dark matter be equipped with a long enough life time and mass degeneracy with a massive decay product to address the S8 tension.